Billie Standish was here - Crocker, Nancy (New York : Simon & Schuster Books for Young Readers, 2007)
When the river jeopardizes the levee and most of the town leaves, Miss Lydia, an elderly neighbor, and Billie form a friendship that withstands tragedy and time.
Keywords: Friendship -- Fiction; Coming of age -- Fiction; Rape -- Fiction